Kesiapan Sekolah dalam Evaluasi Model CIPP pada Kurikulum Merdeka di Smp Shafiyyatul Amaliyyah Medan - Nanda Nurul Baiti; Shynta Sri Wahyuni; Hairil Anwar; Muhammad Amin; Siti Halimah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
By using the CIPP evaluation model at SMP Shafiyyatul Amaliyyah Medan, this study attempted to study the application of the CIPP evaluation model (Context, Input, Process, Product), student learning outcomes in the PAI field of study, and the effectiveness of PAI evaluation. learning process. The level of achievement of learning objectives that have been set at the beginning of the learning process reveals how effective a process is. This test is a subjective exploration using the CIPP model by assessing each part of the setting, information, interactions, and items to achieve a continuously evolving experience. PAI teachers, curriculum representatives, and school principals at SMP Shafiyyatul Amaliyyah Medan were used as research data sources. Observational instruments were used to collect primary data, and interviews and photography were used to collect secondary data. After that, the observation data were analyzed quantitatively, while the interviews and data analysis were analyzed descriptively and qualitatively. The results of the study show that the requirements for implementing learning and learning activities are said to be quite effective when learning is carried out. Keywords: CIPP, Evaluation, PAI Teachers